Initiatives and New Trends Towards Stem Education in Turkey - Yılmaz, Adem; Gülgün, Cihan; Çetinkaya, Murat; Doğanay, Kamil (Redfame Publishing, 2018)
STEM (Science, Technology, Engineering, Mathematics) Education; Is an educational approach that many countries in the world have included in their curricula that allow learners to view the knowledge they learn in science, technology, engineering and mathematics courses, aiming at transforming theoretical knowledge into practice, product and innovative inventions. It is aimed to be able to adapt easily to the qualities of the business life thanks to these skills when the STEM trained individuals enter into the business world, as well as being an approach that is based on giving the skills of STEM education, production and invention. Within the scope of the study, attempts were made to investigate the initiatives and new trends of STEM education from 2010 until the day. Document analysis and thematic content analysis (meta-synthesis) method was used in the research process. Thematic content analysis; Analyze, synthesize and interpret the findings of more than one research on the same subject, with a critical point of view, in contrast to the theme or templates specified and raw data. During the research; Articles, theses, reports and reports which are reached from various sources in the national and international literature have been examined and a wide-scale resource has been created by considering every point related to the contents of the work. The results of the research were examined under various headings and a broad framework was established and recommendations were made.
Keywords: 4. Education